PENGARUH PENGGUNAAN METODE READING WORKSHOP, SQ4R, DAN MOTIVASI BERPRESTASI TERHADAP KEMAMPUAN LITERASI PESERTA DIDIK SEKOLAH DASAR DI SURABAYA - Riski; Mustaji; Nukmatus Syahria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study investigates the effects of the Reading Workshop and SQ4R methods, along with achievement motivation, on the literacy skills of elementary school students in Surabaya. Using a quantitative quasi-experimental design, 189 students were divided into two groups: one employing the Reading Workshop method (92 participants) and the other using SQ4R (97 participants). Data were collected through literacy tests administered at pretest and posttest stages, with average scores increasing from 65.40 (pretest) to 73.47 (posttest). Achievement motivation was also measured to assess its impact on literacy.Results revealed significant differences in literacy improvement between the methods, with Reading Workshop showing superior effectiveness (F = 66.328, p < 0.001). Additionally, students with high achievement motivation demonstrated better literacy outcomes compared to those with low motivation (F = 196.627, p < 0.001). However, no significant interaction was found between the teaching methods and achievement motivation regarding literacy skills (F = 0.163, p = 0.687). The study concludes that while both methods are beneficial, achievement motivation is a more critical factor in enhancing literacy skills. It is recommended that educators focus on increasing students' motivation alongside implementing these methods and suggests further research into various teaching strategies and their long-term effects on literacy development.